2023
DOI: 10.3390/ijerph20031895
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Social Inclusion Interventions for Anxiety and Depression among Adolescents: A Systematic Review

Abstract: Background: Adolescents who are socially excluded are at increased risk of mental health problems such as depression and anxiety. Promoting social inclusion could be an effective strategy for preventing and treating adolescent depression and anxiety. Methods: We conducted a systematic review of intervention studies which aimed to prevent or treat adolescent depression and/or anxiety by promoting social inclusion. Throughout the review we engaged a youth advisory group of 13 young people (aged 21–24) from Ugand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Some studies have hypothesised that social interaction may enhance cognition and improve emotion regulation, reducing mental distress toward happiness 12 . Recent systematic reviews have shown that more social interactions relate to decreases in mental/psychological problems, including depression, anxiety, and sleep problems 16–18 . Moreover, our previous analysis found that sleep problems were negatively associated with happiness among older adults after adjusting for potential confounders 46 .…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Some studies have hypothesised that social interaction may enhance cognition and improve emotion regulation, reducing mental distress toward happiness 12 . Recent systematic reviews have shown that more social interactions relate to decreases in mental/psychological problems, including depression, anxiety, and sleep problems 16–18 . Moreover, our previous analysis found that sleep problems were negatively associated with happiness among older adults after adjusting for potential confounders 46 .…”
Section: Introductionmentioning
confidence: 81%
“…12 Recent systematic reviews have shown that more social interactions relate to decreases in mental/psychological problems, including depression, anxiety, and sleep problems. [16][17][18] Moreover, our previous analysis found that sleep problems were negatively associated with happiness among older adults after adjusting for potential confounders. 46 Gyasi et al 2 have also reported significant associations of poor sleep quality, loneliness, anxiety, and boredom, with happiness.…”
Section: Introductionmentioning
confidence: 90%
“…In response to the first objective, it can be indicated that there is a positive impact on strengthening resilience in vulnerable groups, as well as socio-economic and cultural factors. Therefore, it is important to continue working on the inclusion of these groups and on the design and implementation of effective intervention strategies to promote their resilience [15].…”
Section: Discussion and Analysis Of The Resultsmentioning
confidence: 99%
“…However, this does not imply that they are passive or incapable of overcoming their difficulties. On the contrary, many vulnerable groups demonstrate great resilience in the face of adversity and generate strategies of resistance and social transformation [15].…”
Section: Resilience and Vulnerable Groups: Approaches And Perspectivesmentioning
confidence: 99%
“…Life skills education is an intervention program designed to improve mental wellbeing and strengthen coping skills among children and adolescents (Hunt et al, 2023). The program focuses on teaching responsible decision-making and healthy choices in life (Kaur & Singh, 2023).…”
Section: Life Skills Educationmentioning
confidence: 99%